2020
DOI: 10.1101/2020.04.27.20082149
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

When the storm is the strongest: Healthcare staff’s health conditions and job satisfaction and their associated predictors during the epidemic peak of COVID-19

Abstract: This study reports the physical health, mental health, anxiety, depression, distress, and job satisfaction of healthcare staff in Iran when the country faced its highest number of total active COVID-19 cases. In a sample of 304 healthcare staff (doctors, nurses, radiologists, technicians, etc.), we found a sizable portion reached the cutoff levels of disorders in anxiety (28.0%), depression (30.6%), and distress (20.1%). Age, gender, education, access to PPE (personal protective equipment), healthcare institut… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 25 publications
4
9
0
Order By: Relevance
“…The women's anxiety level (Mean: 4.31±6.02) was significantly higher than that of men (Mean: 2.29±4.81). In the majority of the previous studies, similar to our results, the level of anxiety in women was higher (Pappa et al, 2020;Zhang et al, 2020aLai et al, 2019;Zhang et al, 2020c;. On the other hand, some studies also reported that gender did not affect anxiety levels , Chen et al, 2020Zhang et al, 2020d).…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…The women's anxiety level (Mean: 4.31±6.02) was significantly higher than that of men (Mean: 2.29±4.81). In the majority of the previous studies, similar to our results, the level of anxiety in women was higher (Pappa et al, 2020;Zhang et al, 2020aLai et al, 2019;Zhang et al, 2020c;. On the other hand, some studies also reported that gender did not affect anxiety levels , Chen et al, 2020Zhang et al, 2020d).…”
Section: Discussionsupporting
confidence: 89%
“…When anxiety levels were analyzed in terms of marital status, there was no statistically significant difference between groups in this study (p>0.05). Similarly, previous studies did not found a significant difference in marital status (Zhang et al, 2020a;Chen et al, 2020).…”
Section: Discussionsupporting
confidence: 50%
See 3 more Smart Citations